DEVELOPING ANIMATION-BASED LEARNING MEDIA FOR LISTENING BY USING CANVA APPLICATION - Afriyeni, Shelvina (ELP (Journal of English Language Pedagogy), 2024)
This research aimed to develop animation-based learning media for listening using the Canva application for eleventh-grade students at MAS Tarbiyah Islamiyah Canduang. The need for this research stemmed from three main issues: (1) teachers' reliance on traditional media like loudspeakers and textbooks, without incorporating animation videos; (2) students' need for more interesting and engaging media in the teaching process; and (3) the lack of animation-based teaching media in the learning process. The research employed the 4D (Define, Design, Develop, and Disseminate) version of the Research and Development (R&D) method. The developed media underwent validity testing by three experts (content, language, and construct), scoring 0.82 (valid category). Practicality testing by six practitioners (one teacher and five students) yielded a score of 0.82 (very high category). Finally, effectiveness testing with 15 eleventh-grade students at MAS-TI Canduang resulted in a score of 0.57 (effective category). The research successfully developed an animation-based learning media for listening using Canva, which was validated, practical, and effective for eleventh-grade students at MAS Tarbiyah Islamiyah Canduang.